Report on research, innovation and technological performance in Germany 2018 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2018)
[Foreword] Germany is economically well positioned at the beginning of 2018. The federal budget shows a substantial surplus, and the German economy is regarded as an anchor of stability in the euro zone. Many factors have contributed to this success. One important cause is the high level of investment in research and innovation by the private and public sectors in recent years. Expenditure on research and innovation is an investment in the future, especially in times of rapid technological and economic change. The Commission of Experts for Research and Innovation therefore recommends that the new Federal Government invest more in science, research and innovation in order to secure Germany's role as a leading economic nation in the future. In its 2018 report, the Commission of Experts sets out the aspects that should be taken into account in this context and points to the need to act quickly and decisively. [...]
Keywords: 330